Problems of Learning Islamic Education in Junior High Schools - Simbolon, Parlindungan; Andriani, Widya; Salsabilah, Azizah; Safitri, Yuli Yani; Sarmiah, Lindia (International Journal of Multidisciplinary Research of Higher Education, 2022)
Islamic Education is a science that is taught to students on the basic of the Qur'an and Hadith, but in reality, there are still students who have difficulty understanding the learning of Islamic Religious Education. This study aims to find out what are the problems of learning Islamic Education at Junior High School 3 Ulakan Tapakis. This study uses a qualitative method with a case study. Data sources were taken from twelve informants through direct interviews using a set of interview protocols. The results of these findings found that there were three learning problems in Islamic Education at Ulakan Tapakis 3 Public Junior High School. The three problems are: i) low pedagogical competence, ii) limited study time, and iii) inadequate learning aids. The results of these findings can be used as initial data for future researchers to examine this issue in the context of different issues.